2018
DOI: 10.31557/apjcp.2018.19.12.3427
|View full text |Cite
|
Sign up to set email alerts
|

Melittin Induced G1 Cell Cycle Arrest and Apoptosis in Chago-K1 Human Bronchogenic Carcinoma Cells and Inhibited the Differentiation of THP-1 Cells into Tumour- Associated Macrophages

Abstract: Background: Bronchogenic carcinoma (lung cancer) is one of the leading causes of death. Although many compounds isolated from natural products have been used to treat it, drug resistance is a serious problem, and alternative anti-cancer drugs are required. Here, melittin from Apis mellifera venom was used, and its effects on bronchogenic carcinoma cell proliferation and tumour-associated macrophage differentiation were evaluated. Methods: The half maximal inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…As clearly depicted, FLV-MEL nano-conjugates treatment strongly inhibited the proliferation of OVCAR3 cells, measured by the reduction of G1→S transition as well as the inhibition of the transition from G2 to M phase. These effects could depend on the ability of MEL to suppress the proliferation of cancer cells ( Tipgomut et al, 2018 ; Ceremuga et al, 2020 ; Yao et al, 2020 ) which acts synergistically with FLV ( Hillyard et al, 2002 ; Garwood et al, 2010 ; Hwang et al, 2017 ) even when used at a sub-toxic concentration.…”
Section: Discussionmentioning
confidence: 99%
“…As clearly depicted, FLV-MEL nano-conjugates treatment strongly inhibited the proliferation of OVCAR3 cells, measured by the reduction of G1→S transition as well as the inhibition of the transition from G2 to M phase. These effects could depend on the ability of MEL to suppress the proliferation of cancer cells ( Tipgomut et al, 2018 ; Ceremuga et al, 2020 ; Yao et al, 2020 ) which acts synergistically with FLV ( Hillyard et al, 2002 ; Garwood et al, 2010 ; Hwang et al, 2017 ) even when used at a sub-toxic concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Also many studies show that MEL have a non-selective cytolytic effect, but it was proved that MEL selectively degrades cells' Ras oncogene expression which show overexpressed in 20-50 percent of breast cancers [32][33][34]. Furthermore, studies on normal and lung cancer cells have shown MEL caused lower cytotoxicity to the control human lung fibroblasts cells than to human lung cancer cells [35]. This study suggests that MEL in complexes could have a selective cytotoxic effect on cancer cells, but tests on healthy cells are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent lipid Vybrant DiI, membrane-permeant Green CMFDA cell tracker and orange CMRA Cell Tracker were purchased from ThermoFisher Scientific (#V22885; #C7025 and #C34551, respectively). Penetratin and melittin were purchased from AnaSpec (catalogue # AS-64885) and Sigma-Aldrich (catalogue # M2272), respectively, and used in concentrations 0.25 and 0.5 μM for melittin; and 5 and 10 μM for penetratin, based on earlier studies 68 and 69 , respectively. Melittin and penetratin in concentrations exceeding 1 μM and 10 μM, respectively, caused apparent cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%